Timing of voiding cystourethrography after febrile urinary tract infection in children: a systematic review. Issue 3 (29th August 2019) - Mazzi, Sara; Rohner, Katharina; Hayes, Wesley; Weitz, Marcus
Abstract : Background: Despite a trend towards early voiding cystourethrography (VCUG) after febrile urinary tract infection (fUTI) in children, clinical guidelines do not comment on the optimal timing and current practice varies considerably. Objective: To assess whether the detection rate of vesicoureteric reflux (VUR) in children depends on the time period of VCUG procedure after onset of antibiotic therapy. Methods: MEDLINE, EMBASE and Cochrane Controlled Trials Register electronic databases were searched for eligible studies without language or time restriction (19 November 2018). Inclusion criteria were (1) patients <18 years of age; (2) VCUG performed in patients with fUTI after onset of antibiotic therapy either in the same patient population or in two or more different patient populations within one study at different time periods; and (3) with reported detection rate of VUR. The systematic review was carried out following the recommendations of the Cochrane Collaboration and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Results: Of 4175 records, nine studies were included (number of patients, n=1745) for the main outcome prevalence of VUR by VCUG <8 days compared with VCUG ≥8 days after onset of antibiotic therapy. Pooled overall prevalence of VUR was not significantly different between the early and the late VCUG groups (risk ratio 0.98, 95% CI 0.81 to 1.19). Prevalence of VUR stratified by grade was not significantly different between the two groups. Conclusion: Early VCUG within 8 days after onset of antibiotic therapy does not affect the prevalence of VUR. Trial registration number: CRD42018117545